A SUBCLASS OF BI-UNIVALENT FUNCTIONS RELATED TO SHELL-LIKE CURVES CONNECTED WITH FIBONACCI NUMBERS ASSOCIATED WITH -DERIVATIVE - Nandini, P; Latha, S (TWMS journal of applied and engineering mathematics, 2023)
In this paper, we define a new subclass of bi-univalent functions related to shell-like curves connected with Fibonacci numbers by using (p, q)-derivative and the coefficient estimates, Fekete-Szego inequalities are discussed for the functions belonging to this class. Keywords: Bi-univalent functions, Fekete-Szego inequality, Fibonacci numbers, Shell-like curves and (p, q)-derivative. AMS Subject Classification: 30C45, 30C50.